2008
DOI: 10.7205/milmed.173.7.658
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Pregnancy in the U.S. Military: What We Know and What We Need to Know

Abstract: Adolescent pregnancy is a significant public health problem in the United States, but little is known about this condition in military-affiliated populations. This article reviews what is known about adolescent pregnancy among (1) dependent children of active duty and retired personnel and (2) active duty military personnel. Sparse and conflicting evidence exists regarding the prevalence of, the risk factors for, and the impacts of pregnancy in the dependent child population. Limited evidence regarding active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…17,21 Among both unmarried women and men who responded to the survey, reported condom use with last intercourse was higher for those < 21 compared to 21-25 years old, those with lower educational levels, and service members with enlisted compared to officer rank. Those who reported a higher number of sexual partners in the past year were also more likely to report condom use at last intercourse but less likely to use condoms with each act of intercourse.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,21 Among both unmarried women and men who responded to the survey, reported condom use with last intercourse was higher for those < 21 compared to 21-25 years old, those with lower educational levels, and service members with enlisted compared to officer rank. Those who reported a higher number of sexual partners in the past year were also more likely to report condom use at last intercourse but less likely to use condoms with each act of intercourse.…”
Section: Introductionmentioning
confidence: 97%
“…22 In particular, the rates of STIs in military recruits, young military personnel, and military ethnic minorities are above the national average. 21,30,31 In a study of 1,841 female Marine Corps recruits who were screened for chlamydia, gonorrhea, and trichomoniasis upon entry to the military, 14% tested positive for an STI compared to 8% of similar aged women in the general population tested during the same time frame. 29 In studies in which asymptomatic military personnel were randomly screened for STIs, the prevalence of chlamydial infection was between 5% and 10% overall.…”
mentioning
confidence: 99%
“…6 These adolescents' risk profiles for pregnancy, birthing, and delivery type are poorly understood. 7 Prior study of the DoD suggests that CD rates among all military-affiliated young adults are lower than among young adults in the national population, 8 but it is unknown whether this is the case specifically of the dependent children of service members. The purpose of this study was to investigate delivery trends among adolescents who were covered by TRICARE health plans because of their parents' DoD affiliation.…”
Section: Introductionmentioning
confidence: 98%
“…5 Evidence suggests that active duty women frequently engage in high-risk sexual behaviors, defined by the U.S. Preventive Services Task Force as using condoms inconsistently, having multiple concurrent partners, having a new partner, or having sex while under the influence of alcohol or drugs. 6 For example, a number of surveys with active duty women suggest that only a minority report using condoms regularly [7][8][9] and that nearly a third report having sex under the influence of alcohol or drugs. 10,11 Studies have consistently demonstrated higher rates of chlamydia infections among active duty compared with civilian women, although these results may be at least partially due to differential screening rates.…”
mentioning
confidence: 99%